School Facilities Management System (SFMS) / Gan Hui Hoon - Gan , Hui Hoon (2000)
Computer information system and computer applications are very important to all the organizations. Thus the government is introducing the MSC or Multimedia Super Corridor. It is meant to develop Malaysia into a regional and international technology and telecommunications hub in 2020. The MSC will propel the transfer of technology and become the test bed for R&D in high-tech industries. There are seven-flagship applications in MSC, and Smart School is one of the seven flagship applications in MSC School Facilities Management System will be an example of what the function of facilities management in Smart School will be like. The facilities management function is one of the ten functions of Smart School implementation in Malaysia. This report is about the development School Facilities Management System, SFMS. The system provides the facility to keep track of the usage of facilities in schools. It includes an inventory module that will inventories special equipments and apparatus in special rooms. The system will be able to remain the user to do maintenance for the needed equipments. There are seven chapters in this report, which includes Introduction, Literature Review, System Analyst, System Design, System Implementation, Testing, and System Evaluation and Conclusion. The first four chapters are considered as phases that a system analysts need to go through before one can come out with clear and concise definitions of all the functional and non-functional requirements that are needed to develop a good application later in the future. The last three chapters are the remaining phases of system development, which uses all findings and information, gather in the earlier four chapters.